2018
DOI: 10.1039/c7sm02465g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymer–nanoparticle interactions on the viscosity of unentangled polymers under extreme nanoconfinement during capillary rise infiltration

Abstract: We explore the effect of confinement and polymer-nanoparticle interactions on the viscosity of unentangled polymers undergoing capillary rise infiltration (CaRI) in dense packings of nanoparticles. In CaRI, a polymer is thermally induced to wick into the dense packings of nanoparticles, leading to the formation of polymer-infiltrated nanoparticle films, a new class of thin film nanocomposites with extremely high concentrations of nanoparticles. To understand the effect of this extreme nanoconfinement, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 61 publications
8
76
0
Order By: Relevance
“…There are a few exceptions to these apparently general trends that are worth emphasizing. Recent work by Fakhraai et al [35] found that for densely packed, but random NP assemblies, T g shifts were larger for longer chain length polymers, a finding that is consistent with our assertion that the relevant control parameter is r/R g . However, the precise value of r/R g is hard to estimate here since the NPs are in contact with each other.…”
Section: Interfacial Regionsupporting
confidence: 92%
“…There are a few exceptions to these apparently general trends that are worth emphasizing. Recent work by Fakhraai et al [35] found that for densely packed, but random NP assemblies, T g shifts were larger for longer chain length polymers, a finding that is consistent with our assertion that the relevant control parameter is r/R g . However, the precise value of r/R g is hard to estimate here since the NPs are in contact with each other.…”
Section: Interfacial Regionsupporting
confidence: 92%
“…[ 11 ] Capillary rise infiltration (CaRI) recently has been used to induce imbibition of high molecular weight species such as polymers and oligomers into nanoporous media such as nanoparticle packings and assemblies. [ 12 ] Here, we induce infusion and retention of silicone oil in the nanostructure of ZnO NW arrays via capillarity to produce stable SLIPS. The advantage of ZnO NW arrays is that the morphology of the porous structure can be varied by changing the orientation of NWs.…”
Section: Resultsmentioning
confidence: 99%
“…This trend is consistent with previous CaRI studies. [ 1,2,23,31 ] In addition, the sum of the thickness of the neat SiO 2 layer and PS‐infiltrated SiO 2 layer is almost the same with the initial thickness of the SiO 2 layer (≈150 nm), indicating that the infiltration does not affect the structure SiO 2 layer. Thus, the packing fraction of the SiO 2 NPs remains high during and after the infiltration of the PS.…”
Section: Resultsmentioning
confidence: 93%
“…Our prior work has shown that many types of polymers readily infiltrate packing of SiO 2 NPs via capillarity due to the high surface energy of SiO 2 . [ 23 ] Thus, we believe particles made of a wide range of linear polymers can be used to form heterostructured PINFs with cavities using our approach. However, we believe the size of the smaller inorganic NPs should be small enough to slide into the interstices between the larger polymer particles to enable the formation of the heterostructured PINFs with cavities.…”
Section: Resultsmentioning
confidence: 99%